A novel Home Exercise Assessment Tool (HEAT) to assess recall and performance: A reliability study. (1st February 2023) - Halfpap, Joshua; Allen, Christopher; Rhon, Daniel I.
ABSTRACT: Background: A reliable and valid tool to measure short-term recall does not exist. Objective: The purpose of this study was o assess the reliability of a novel tool designed to evaluate the immediate recall and performance of prescribed exercises. This reliability study was secondary from a parent randomized controlled trial. Methods: Patients ages 18 to 65 with low back or unilateral knee pain longer than 6 weeks, reporting to a primary care or physical therapy clinic at one large military hospital. Participants were randomized into one of four groups based on number of exercises and type of instruction. The Home Exercise Assessment Tool (HEAT) is scored along an ordinal scale, (zero = low; three = high performance), with 2+ equal to meeting the intent of the exercise. Reliability of testing was assessed using a pool of four raters. Results: The interrater reliability of the HEAT performed on 30 participants (9 females, and 21males, mean age 36.7 (SD = 11.7)) and eight participants during pilot testing demonstrated moderate to good reliability (ICC = 0.66–0.77). Intrarater reliability during pilot testing was excellent (ICC = 0.93–0.96). Conclusion: The HEAT demonstrated moderate to good interrater and excellent intrarater reliability. This tool is unique in that it assesses both recall and adherence, and merits further testing in other settings.